Penyuluhan Gizi Seimbang Bagi Orang Dewasa Pada Masa Pandemi Covid-19 Di Dusun V-A Desa Sambi Rejo - Athira Demitri; Agnes Sry Vera Nababan; Yulita Yulita; Rosalinda Rosalinda; Mayumi Swardani (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
The increasing Covid-19 pandemic has resulted in a world health crisis. The Covid-19 virus can attack various age groups, starting from babies, toddlers, children, elementary school children, adults and even those who are very vulnerable, namely the elderly and elderly. The World Health Organization (WHO) has recommended a balanced nutritional menu during childhood. covid-19 pandemic. This means that every food menu must include complete nutrition, including macronutrients such as carbohydrates, protein, fat, as well as micronutrients from vitamins and minerals. Therefore, it is necessary to provide education through counseling about balanced nutrition for adults during the Covid-19 pandemic. This activity will be carried out on March 25 2022 in V-A Hamlet, Sambi Rejo Village, Binjai District. This extension targets 30 hamlet communities. The activity organizer started the education by explaining about balanced nutrition, Covid-19, and sources of nutrients that can be consumed during the Covid-19 pandemic to increase immunity and recovery. The activity organizer provided counseling for approximately 60 minutes and continued with a question and answer session. In this session, 5 people asked questions and discussed their experiences in consuming certain sources of nutrients during the Covid-19 pandemic.